Confident Parents for Easier Children: A Parental Self-Efficacy Program to Improve Young Children's Behavior - Bénédicte Mouton; Laurie Loop; Marie Stiévenart; Isabelle Roskam (MDPI AG, 2018)
This study presents the effects on children’s behavior of Confident Parents, a focused parenting program targeting parental self-efficacy. This parenting program aims to improve child behavior through the enhancement of parental self-efficacy. Confident Parents was experimentally tested on a total sample of 80 parents of three-to-six-year-old preschool aged children with moderate to clinical levels of externalizing behavior. Thirty-seven parents participated in the program, and were compared with a waitlist control group (n = 43). The intervention consisted of eight weekly group sessions. Effect sizes were evaluated through both observational and parent-report measures on the child’s behavior, as well as self-reported parental self-efficacy at pretest, post-test, and a four-month follow-up. Through a multi-level analysis, predictors of the change in the child’s behavior were identified. The moderating effect of socio-economic risk and externalizing behavior at baseline were also included in the analysis. Results show that Confident Parents improved the child’s behavior, both reported by parents and, to a lesser extent, when observed in interaction with the parent. Children with higher levels of behavior difficulty benefited more while those with socio-economic risk benefited less from this program. These results illustrate that focusing a parenting program on improving self-efficacy is effective to reduce externalizing behavior in children. This underdeveloped treatment target is worthy of investigation in parenting intervention research.